Anchoring learning: A grounded theory on nurturing capacities of student achievers - Mangiduyos, Gladys P. (Animo Repository, 2012)
A grounded theory of nurturing capacities evolved from the twenty (20) high performing students and alumni from Wesleyan University-Philippines. Data analysis followed the classic grounded theory methodology of Glaser and Strauss. Emerging a framework, it explains the process of learning among student achievers, what sustains them in performing highly in every dimension and how this has become a never ending venture for them. It unveiled how they understand the meaning of their learning process. Anchoring learning process category shows how it sustains and encompasses other distinct yet interrelated categories of learning process which is happening among the student achievers. It is comprised of the following which consequently give the student achievers strong motivation and eagerness in nurturing their capacities: (1) affecting process in learning (2) firming process in learning (3) manifesting rootedness process in learning. Revealing a vast and far-reaching implications, the process described in the framework has implications for Educational Leadership and Management as a tool for facilitating learning. It provides firm grounds for instructional leadership and mentoring process.